Fourier-Domain Optical Coherence Tomography Signal Analysis and Numerical Modeling - J. Kalkman (International Journal of Optics)
In this work the theory of the optical coherence tomography (OCT) signal after sampling, in dispersive media, with noise, and for a turbid medium is presented. The analytical theory is demonstrated with a one-dimensional numerical OCT model for (single) reflectors, dispersive media, and turbid media. For dispersive media the deterioration of the OCT axial resolution is quantified analytically and numerically. The OCT signal to noise ratio (SNR) is analyzed in the Fourier-domain and simulated with the numerical model. For an SNR based on the OCT intensity the conventional shot noise limited SNR is derived whereas for an SNR based on the OCT amplitude a 6.7 dB higher SNR is demonstrated. The OCT phase stability is derived in the Fourier-domain as 2SNR−1 and is validated using the numerical OCT model. The OCT single scattering model is simulated with the one-dimensional numerical model and applied to the simulation of an OCT image of a two-layered sample.